Undergraduate Students’ Perceptions toward Self-Assessments - Karina Shagitha; Anita Kurniawati Hadiyanto (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2022)
In the current education context that encourages students to be independent learners, self-assessments have gained more attention as one of the effective ways to support self-learning. However, teachers in Indonesia seem hesitant to use self-assessments because they assume that students cannot understand and perform self-assessments. Therefore, the research is aimed to know about undergraduate students' perceptions toward self-assessments, which can result in knowing students' comprehension of self-assessments. The research was conducted at an English Language Education Program (ELEP) from one of the private universities in Central Java, which involved 42 students from the 2018 academic year who had passed Teaching Skills Courses (Teaching English for Young Learners, Teaching English for Adult Learners, and Teaching English for Specific Purposes). A questionnaire consisting of close-ended and open-ended questions was used to collect the data, and the data were analyzed using statistical analysis and content analysis methods. From the results, it was found that the participants reacted positively toward self-assessments. The participants felt content and helped when doing self-assessments, and they also knew the benefits and the importance of it. Furthermore, it was found that they were able to carry out self-assessments appropriately and showed their preference for self-assessments, such as comparing with criteria or making reflections. Therefore, it can be concluded that the teachers' previous assumptions can be considered inaccurate. The study is hoped to help teachers consider implementing self-assessments more in their courses and help them design suitable self-assessments.